Penatalaksanaan Herpes Zoster pada Pasien Wanita Usia Produktif : Sebuah Laporan Kasus - Arfa Salma Firnandya; Reni Zuraida (Medula, 2026)
Herpes zoster is caused by the reactivation of latent Varicella-zoster virus (VZV) following primary varicella infection. Although it is more common among older adults, it may also occur in productive-age individuals with risk factors such as psychological stress, sleep deprivation, and unhealthy lifestyles. This case report describes the comprehensive management of herpes zoster in a productive-age woman. A 19-year-old woman presented with painful, pruritic, and burning vesicular eruptions on the right posterior lumbar region for four days. Dermatological examination revealed multiple erythematous vesiculobullous lesions with a unilateral dermatomal distribution. The patient had a history of childhood varicella, high academic stress, inadequate sleep, low physical activity, and poor dietary habits. A clinical diagnosis of herpes zoster of the right posterior lumbar region was established. The patient received oral acyclovir 800 mg five times daily, topical acyclovir 5%, paracetamol, cetirizine, and vitamin C for seven days. Non-pharmacological interventions included education regarding the disease, stress management, sleep improvement, physical activity, balanced nutrition, and family support. Follow-up evaluation demonstrated reduced pain, pruritus, and burning sensation, drying of lesions without new eruptions, and improved knowledge and health-related behaviors. A comprehensive approach integrating antiviral therapy, patient education, lifestyle modification, and family support resulted in favorable clinical outcomes and may help prevent complications and recurrence in productive-age patients with herpes zoster.